Language Practices in English Classrooms - Sundqvist, Pia; Sandlund, Erica; Källkvist, Marie; Gyllstad, Henrik (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Sundqvist, Sandlund, Källkvist, and Gyllstad have edited a timely reprint that will help to guide the future of English language teaching and learning. This comprehensive and lucidly written volume brings together research on English classroom practices from all levels across the globe with the aim of enhancing our understanding of current developments. All chapters are theoretically informed, as the reprint is both practical in its style and orientation, and pedagogically astute in the recommendations offered. This volume is a welcome resource for teachers, student teachers, teacher educators and researchers around the world.